DETERMINAN PENGAMBILAN KEPUTUSAN RUMAHTANGGA DALAM MENYEKOLAHKAN DAN MEMPERKERJAKAN ANAK : STUDI KASUS DI KABUPATEN SUMEDANG - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The purpose of this study is to explore and identify the socio-economic aspects of the population that influence educational decision making through service activities that are in harmony with the problems of education and child labor, in Cibeusi Village, Jatinangor District, Sumedang Regency. The method implemented in this service is through assistance, workshops, socialization, participatory communication and other activities. The field of program activities or the theme of this service activity is education and counseling relating to children's education, educational activities and child labor. Based on the results of service shows that the socio-economic aspects of the family that influence education decision making, especially in the Cibeusi Village, Jatinangor Sub-District, Sumedang Regency are income. Revenue is the most important factor in determining household decisions in sending their children to school. Other factors that influence children's educational decision making are the parents' educational background. Generally the level of education in the Cibeusi Village area is on average elementary to junior high school education. This finding indicates that the level of parental education greatly influences the level of children's school participation and also the child's desire for school. In such conditions, parents need to play an active role in teaching learning styles such as what is suitable for students so that children want to go to school and also student learning outcomes increase.